Neurotrophic properties and the de novo peptide sequencing of edible bird's nest extracts. (December 2019) - Yew, Mei Yeng; Koh, Rhun Yian; Chye, Soi Moi; Zainal Abidin, Syafiq Asnawi; Othman, Iekhsan; Ng, Khuen Yen
Abstract: Neural stem cells (NSC) are multipotent precursor cells in the neurogenic regions of the brain which respond to trophic factors to achieve functional recovery from neurodegenerative diseases. Edible bird's nest (EBN) is a salivary product of Aerodramus swiftlets and may contain potent neurotrophic compounds. Crude and water extracts of EBN were shown to have neurotrophic properties by promoting proliferation and migration of the NSC model, embryonic mouse neuroectodermal cells (NE-4C). Neuronal differentiation of retinoic acid-primed NE-4C was also increased after being treated with EBN extracts. Using de novo peptide sequencing with tandem mass spectrometry, a total of 29 proteins were identified from EBN extracts. It is suggested that the repulsive guidance molecule domain family member B, which has been shown to promote neurite extension and axonal growth, as well as proteins involved in the process of cell proliferation and migration such as protein lin-9 and hyaluronan mediated motility receptor might be involved in the neurotrophic effects of EBN extracts. Other proteins found in EBN extracts were known to have potential roles in immunity, extracellular matrix formation, cell survival and apoptosis, antioxidation, and common cellular processes, which may be implicated in other EBN studies. Seven hypothetical proteins suggested using the PEAKS Studio 7.0 software did not have a match in the Swiss-Prot database, which may need to be further characterized in the future. In conclusion, this study described the neurotrophic properties of EBN extracts and supports the use of EBN as a potential functional food against neurodegenerative diseases. Highlights: EBN increased NE-4C proliferation and migration rate. Neurogenesis was promoted in retinoic acid-primed NE-4C cell after EBN treatment. Protein in raw and water extracts of EBN was studied using de novo peptide sequencing. EBN may act as a nutraceutical food in the treatment of neurodegenerative diseases.